2019
DOI: 10.1678/rheology.47.105
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Evaluation of Carbon Nanotube Redistribution in Polymer Melt

Abstract: We investigated changes to the linear viscoelastic properties of a mixture comprising polycarbonate (PC) containing 3 wt.% of a multiwalled carbon nanotube (MWCNT) and high-density polyethylene (HDPE), also containing 3 wt.% MWCNT, during post-processing annealing. The oscillatory shear moduli-i.e., the storage modulus G′ and the loss modulus G′′-gradually increased with residence time in a rheometer (i.e., annealing). The samples were prepared by compression-molding at low temperature, during which the MWCNTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…One example is the addition of carbon nanotubes (CNT) to polyethylene (PE) 17,21 . CNTs show strong nucleating activity for PE 23 and orient to the flow direction, 24 so a crystalline structure similar to that of the shish‐kebab is easily formed. This is referred to as a ‘nanohybrid shish‐kebab’ 17 .…”
Section: Introductionmentioning
confidence: 99%
“…One example is the addition of carbon nanotubes (CNT) to polyethylene (PE) 17,21 . CNTs show strong nucleating activity for PE 23 and orient to the flow direction, 24 so a crystalline structure similar to that of the shish‐kebab is easily formed. This is referred to as a ‘nanohybrid shish‐kebab’ 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The density of the composite was approximately 2300 kg m –3 . Further details were described in the literature …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the details in the crystalline structure of PE grown on the MWCNT surface are still unknown . Because the relaxation time of the MWCNT orientation is long compared with the characteristic time under the flow, that is, the inverse of the shear rate, MWCNTs can behave like shish at conventional processing operations. We found that MWCNTs enhance the chain orientation of HDPE to a surprising extent.…”
Section: Introductionmentioning
confidence: 99%